Exploring the Influence of Digital Media on Reading Habits - Ihsan, Fajri; Zulfikar, Fahmi; Syam, Awal (Journal Social Humanity Perspective, 2024)
Digital media's explosive expansion and speedy appearance have profoundly changed traditional reading habits and how people interact with textual content. This study examines the advantages of conventional reading in the historical background, the technological developments that led to the emergence of digital media, and the resulting shifts in reading habits. Findings show that the widespread use of digital platforms and devices has significantly decreased sustained reading and increased desire for shorter, bite-sized content. Furthermore, the study addresses the implications of these changes for education and draws attention to the cognitive difficulties that come with reading on digital devices, including reduced attention spans and greater multitasking. The study emphasizes the necessity of a well-rounded strategy that preserves the richness and engagement of conventional reading while utilizing the benefits of digital media.